"Blood pressure monitoring should be a habit": adaptation of the Check. Change. Control. program for Asian American older adults, from group-based in-person to one-on-one telephone delivery. Issue 6 (15th January 2021) - Jang, Sou Hyun; Brown, Emily V R; Lee, Eun Jeong; Ko, Linda K
Abstract: Asian Americans have the lowest rate of awareness about hypertension, including controlled hypertension, among all racial/ethnic groups in the USA. A high proportion of Asian American older adults have limited English proficiency (LEP) and hypertension. This study adapted the Check. Change. Control. (CCC) program, a community-based intervention for hypertension control delivered in a face-to-face group setting, to phone-based delivery and evaluated the acceptability of the program among Asian American older adults with LEP. Thirteen participants received phone-based educational sessions on hypertension control over 4 months. After 4 months of interventions, we interviewed the 13 Asian American older adults and 4 counselors to examine the acceptability of the adapted CCC program. Both Asian American older adults and counselors found the phone-based delivery of the CCC program to be acceptable, and some participants recommended holding an in-person meeting before telephone delivery to review the program content and clarify information. Future study needs to explore the effectiveness of the phone-based delivery of the program on blood pressure management among larger groups of Asian American older adults. Abstract : Telephone-based delivery of a hypertension control intervention is acceptable among Asian American older adults with limited English proficiency.